2014
DOI: 10.1530/eje-14-0327
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of long-term safety of dual-release hydrocortisone replacement administered once daily in patients with adrenal insufficiency

Abstract: ObjectiveThe objective was to assess the long-term safety profile of dual-release hydrocortisone (DR-HC) in patients with adrenal insufficiency (AI).DesignRandomised, open-label, crossover trial of DR-HC or thrice-daily hydrocortisone for 3 months each (stage 1) followed by two consecutive, prospective, open-label studies of DR-HC for 6 months (stage 2) and 18 months (stage 3) at five university clinics in Sweden.MethodsSixty-four adults with primary AI started stage 1, and an additional 16 entered stage 3. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 22 publications
2
42
0
1
Order By: Relevance
“…This treatment proved to be safe and was well-tolerated during 24 consecutive months of therapy in patients with PAI (8). In the initial 3 months trial, this new modified release HC showed an improvement in cardiovascular risk factors, glucose metabolism, and HRQoL in comparison with conventional treatment with trice daily HC (7).…”
Section: Introductionmentioning
confidence: 94%
“…This treatment proved to be safe and was well-tolerated during 24 consecutive months of therapy in patients with PAI (8). In the initial 3 months trial, this new modified release HC showed an improvement in cardiovascular risk factors, glucose metabolism, and HRQoL in comparison with conventional treatment with trice daily HC (7).…”
Section: Introductionmentioning
confidence: 94%
“…Patients with hypopituitarism with partial/total ACTH deficiency and on suboptimal cortisol therapy may develop symptoms of cortisol deficiency upon initiation of growth hormone therapy due to inhibition of 11-betahydroxysteroid dehydrogenase-type-1 [6][7][8][9].…”
Section: Treatment Of Secondary Adrenal Insufficiency [6-9]mentioning
confidence: 99%
“…Nilsson AG et al [9] concluded favorable results on safety and tolerance of DR-HC during 24 months of therapy [9].…”
Section: Once Daily Long Acting Hydrocortisone Therapymentioning
confidence: 99%
“…The long-term safety data are reassuring and of great values as there was an indication of increased reporting of mild adverse events after the switch from conventional TID to DR-HC [10]. Careful analysis of the association between the pharmacokinetic profile and adverse event reporting suggested that this initial increase in number of adverse events was related to increased awareness among the patients during the therapeutic change and not due to the change in cortisol exposure or time exposure profile [12].…”
mentioning
confidence: 96%
“…In 11 patients with concomitant diabetes mellitus (DM), a reduction in HbA1c was observed with DR-HC compared with TID. After the pivotal trial, patients entered a long-term prospective openlabelled safety trial that could show safe outcome with the use of the DR-HC [12]. The long-term safety data are reassuring and of great values as there was an indication of increased reporting of mild adverse events after the switch from conventional TID to DR-HC [10].…”
mentioning
confidence: 99%